Real-Time Rainfall Prediction in Kathmandu, Kapan Area using Sensor Data with Machine Learning and Linear Regression - Paneru, Biplov; Paneru, Bishwash (Journal of Soft Computing Paradigm, 2023)
The rainfall in the Kapan area is one of the most challenging aspects due to flooding in many parts of the area. The rainfall in the area of Milanchowk, Kapan, Nepal is one of the most challenging aspects that all the researchers, engineers, and geologists are trying to figure out. The research work is simply forecasting the weather and predicting it using machine learning techniques. The data from nearly half a month is collected in real time using sensor data through raspberry pi computer, and then the data is cleaned and processed for linear regression model-based precipitation. The work is carried out with a case study of the area, with appropriate steps taken to monitor in real-time and process the data accordingly.